Comparative Study of Cellulase of Trichoderma viride and Aspergillus niger - Khan, M.R.; Subhani, A. (Asian Journal of Chemistry, 2012)
Aspergillus niger and Trichoderma viride were grown in wheat bran medium by both surface culture and submerged culture techniques. Some characteristics of cellulases produced under different conditions were compared. The results indicated that Aspergillus niger produces cellulase more than that which produces Trchoderma viride in surface culture On the other hand, Trichoderma viride produces cellulase more than that produced by Aspergillus niger in submerged culture. The comparison of profiles indicated that the production of cellulase by surface culture technique is better than that by the submerged culture technique. The temperature optima of cellulase of Aspergillus niger and Trichoderma viride were 50 and 30 ºC, respectively. The cellulase of Aspergillus niger was rather more thermostable.